A down converting serine-functionalised NaYF4:Ce3+/Gd3+/Eu3+@NaGdF4:Tb3+ photoluminescent probe for chemical sensing of explosive nitroaromatic compounds. (12th November 2020) - Tashi, Lobzang; Singhaal, Richa; Kumar, Manesh; Sheikh, Haq Nawaz
Abstract : In this contribution, we explored a novel serine-functionalised NaYF4 :Ce 3+ /Gd 3+ /Eu 3+ @NaGdF4 :Tb 3+ core–shell nanophosphor as a down-converting photoluminescent probe for efficient sensing of nitroaromatic explosives. Abstract : In this study we demonstrate a Ser-CS (serine-functionalized NaYF4 :Ce 3+ /Gd 3+ /Eu 3+ @NaGdF4 :Tb 3+ core shell) nanophosphor for the effective detection of nitroaromatic derivatives. The Ser-CS nanophosphors have a remarkable sensitivity towards electron deficient nitroaromatics. viz., ortho -nitrophenol (2-NP), para -nitrophenol (4-NP), 2, 4-dinitrophenol (2, 4-DNP), picric acid (PA), 1, 3-dinitrobenzene (1, 3-DNB) and para -nitrotoulene (4-NT). The presence of serine amino acid residues on the core–shell surface inhibits aggregation and increases the stability and solubility of the probe in aqueous medium. The Ser-CS exhibits strong and sharp emission peaks around 493, 548, 594, 610 and 700 nm. Importantly, the peak centred at 610 nm exhibits a noticeable quenching effect on addition of nitro-compounds to the aqueous solution of the nanophosphor. The high quenching constant ( K SV ) (4.364 × 10 4 M −1 ) and low detection limit (1.67 ppm) for PA imply the high selectivity and sensitivity towards PA relative to other explosive nitroaromatics compounds.